Avaliação da Apoptose e Produção de TNF-a no Câncer de mama: correlação com fatores prognósticos - Farias, Rogério Estevam (2004)
Tumor necrosis factor alpha (TNF-α) is a cytokine recognized as an important mediator of apoptosis process and also showed citotoxicity against breast malignant tumor cells. In the present study, the presence of tumor apoptotic cells was investigated in grade I, II and III invasive breast cancer and compared with another prognostic factors. In situ detection of tumor apoptotic cells was investigated by direct immuno-peroxidase of digoxigenin-labeled genomic DNA. The production of TNFα, tumor cell proliferation, hormonal receptor, c-erbB-2 and p53 was investigated using immuhistochemical procedure. Our data demonstrated that patients with high apoptotic rate correlates with higher levels of cell proliferation, positive p53 expression, negative hormonal expression and high grade breast cancer. Otherwise patients with a clinical history of cancer recurrence and metastasis presented a lower number of cancer apoptotic cells, higher tumor proliferation rate and lower expression of TNF-α by inflammatory cells than that observed among patients diagnosed with the same histopathological type of breast cancer but with absence of tumor recurrence and metastasis. Taken together the results suggested that the rate of apoptosis reflect degrees of histological breast cancer and correlates with another prognostic factors. In addition, it is also possible that TNF-α produced by tumorassociated inflammatory cells play an important role in the control of apoptosis of breast cancer cells and clinical behavior.